2018
DOI: 10.1016/j.cgh.2018.02.022
|View full text |Cite|
|
Sign up to set email alerts
|

Prediagnosis Use of Statins Associates With Increased Survival Times of Patients With Pancreatic Cancer

Abstract: Regular statin use before diagnosis of pancreatic cancer was associated with modest increases in survival times in 2 large prospective cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The finding that atorvastatin suppresses ADM and, when combined with BET inhibition, can reduce tumor growth aligns with an extensive epidemiologic literature that suggest that statins, which are widely prescribed clinically as cholesterol-lowering agents, may also exert anticancer effects (55). Although analysis of two large prospective studies found no difference in pancreatic cancer risk between regular and non-regular statin users (56), a modest increase in median survival was observed for patients who had been regular statin users for the 2 years prior to cancer diagnosis (57). In addition, numerous prior studies have found that statin use correlates with extended survival, particularly if precedent to pancreatic cancer diagnosis and in a high-dose regimen (55).…”
Section: Researchmentioning
confidence: 57%
“…The finding that atorvastatin suppresses ADM and, when combined with BET inhibition, can reduce tumor growth aligns with an extensive epidemiologic literature that suggest that statins, which are widely prescribed clinically as cholesterol-lowering agents, may also exert anticancer effects (55). Although analysis of two large prospective studies found no difference in pancreatic cancer risk between regular and non-regular statin users (56), a modest increase in median survival was observed for patients who had been regular statin users for the 2 years prior to cancer diagnosis (57). In addition, numerous prior studies have found that statin use correlates with extended survival, particularly if precedent to pancreatic cancer diagnosis and in a high-dose regimen (55).…”
Section: Researchmentioning
confidence: 57%
“…In line with this conclusion, recent epidemiological studies imply that the use of statins is associated with beneficial effects in PDAC [3847], and other malignancies [48]. Although a recent study failed to detect an effect of statins in lowering PDAC risk [73], a follow up study of the same data reported an increased survival in PDAC patients with regular pre-diagnosis use of statins [74]. Taken together with the findings presented here and the lack of efficient strategies to oppose PDAC development, these studies warrant a comprehensive evaluation of the lipophilic statins in the primary or secondary chemoprevention of this devastating disease.…”
Section: Discussionmentioning
confidence: 85%
“…the cholesterol reducing drugs called statins, lower the levels of farnesyl substrate and reduce the amount of K-RAS that can localize in the PM [3]. Many published meta-analyses have shown that statin use enhances the survival time of pancreatic cancer patients, with one study also linking the AMPK activator metformin to prolonged survival [6][7][8][9][10]. Maintenance of K-RAS on the PM additionally requires the chaperone protein PDEδ [11].…”
Section: Introductionmentioning
confidence: 99%